Antiretroviral Prophylaxis for HIV Prevention in Heterosexual Men and Women - Baeten, Jared M; Donnell, Deborah; Ndase, Patrick; Mugo, Nelly R; Campbell, James D; Wangisi, Jonathan; Tappero, Jordan W; Bukusi, Elizabeth A; Cohen, Craig R; Katabira, Elly; Ronald, Allan; Tumwesigye, Elioda; et al. (The New England journal of medicine, 2012)
In this study of 4758 HIV-1–serodiscordant heterosexual couples in Kenya and Uganda, daily antiretroviral prophylaxis (with tenofovir or emtricitabine–tenofovir) in the HIV-1–negative partner significantly decreased the risk of HIV infection. The use of antiretroviral medications for the prevention of HIV type 1 (HIV-1) transmission is a promising strategy for reducing the spread of HIV-1. 1 – 4 Antiretroviral treatment for persons infected with HIV-1 provides important clinical benefits and substantially reduces infectiousness. 5 – 7 Antiretroviral prophylaxis is a potential HIV-1–prevention strategy for those not yet infected with HIV-1, administered either as postexposure prophylaxis after high-risk occupational or nonoccupational exposure or as preexposure prophylaxis in those with ongoing HIV-1 exposure. 8 , 9 The rationale for antiretroviral prophylaxis in persons with ongoing exposure is based on its efficacy in infants exposed to HIV-1 during birth and . . .